Efisiensi Persediaan Kantong Semen Berbasis Metode MIN-MAX, EOQ, dan TWO-BIN di Packing Plant PT AKA - Muhammad Ryfqie Alamanda Rozaq; Nina Aini Mahbubah (SIGMA TEKNIKA, 2022)
PT AKA  is a multinational enterprise engaged in the cement industry. One of the supporting raw materials in cement production is cement bags. Demand for cement bags is directly proportional to the demand for cement. The production division has been experiencing the problem of inefficiency in determining the supply of cement bags. This study aims to evaluate the company's policy in controlling the supply of raw materials for cement bags by comparing the 3 Min-Max, EOQ, and Two-Bin methods. Quantitative data were used: demand for cement bags, storage, and ordering costs. Forecasting data calculations were performed using Minitab software. The results showed that the Min-Max method produced the optimal efficiency with a total inventory cost of Rp. 119,107,700 for 40 kg cement bags, and Rp. 35,528,720 for 50 kg cement bag.